Tapembol in physical education classes: from play to unconventional sport (Research, Society and Development, 2023)
The objective of the study was to investigate the perception of students about the Tapembol modality of a school in Santana-AP and to present a report of the modality's creator about the sport. A qualitative, exploratory and descriptive study was carried out. Information was sought in some databases using the word Tapembol and only two scientific articles dealing with the subject were identified. The research was organized in three stages: signature of the TCLE by the students' parents, signature of the Term of Assent by the students and data collection. The sample consisted of 200 elementary school students who answered a questionnaire about the modality researched. The results indicated that the students still know little about the modality and that there is a great interest on the part of the students in participating in the classes and in the theme of Tapembol. The results also indicated, as reported by the modality's creator, that Tapembol is a sport that is easy to perform, inclusive and with good gameplay, characteristics that facilitate the participation of students in classes. It is concluded that Tapembol in Physical Education classes is still an expanding modality and that there is a need for further studies to disseminate and know more about this sport.